Desenvolvimento — um conceito ultrapassado ou em renovação? Da teoria à prática e da prática à teoria - Rogério Roque Amaro (Cadernos de Estudos Africanos)
The concept of development has been one of the most important and polemical in the Social Sciences. Whilst it is widely considered to mobilise the will for change and transformation in both societies and individuais, it has also served to assess and classify their level of progress and well-being. Since the concept is present in various disciplines, it has produced different theories of change but has also been used to galvanise and assess practices and interventions. From this point of view, it is one of the concepts which is most able to engender dialogue (or confusion) between subject areas and to link or separate theory and practice. Over the last 60 years, and particularly the last 30 years, the concept has appeared in different versions, becoming more complex and less linear in how it is both conceived and applied. This complexity has been enriched by the contribution of several disciplines and by the experience provided by a variety of practices. This in turn has meant that it presents many challenges, both in terms of the interdisciplinary approach it requires and in terms of the strategies and methods of intervention it implies. For this reason, it has also become the object of new polemics, but it is also able to generate new formulations and challenges and to motivate renewed interest.